Participatory Action in Unraveling Farmers’ Dependence Towards Self-Sufficiency of Shallot Seeds in Pejok Village, Kedungadem Bojonegoro - Muhammad Nuril Huda; Nur Khoironi; Khusnul Isma Nuriza (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2021)
Pejok Village is one of the largest shallot producers in Bojonegoro Regency. However, there are obstacles faced by farmers. The shallot farmers are relying on other regions for shallot supply. This study aimed to 1) identify farmers’ problems with shallot seedlings from outside the region, 2) find solutions to decrease shallot farmers’ dependency, and 3) take action in building farmers’ independence towards self-sufficiency in shallot seeds. This study applied a Participatory Action Research (PAR) approach that involved community interaction in identifying problems and coming up with solutions. Two actions were taken to solve the farmers’ problems: 1) training on the cultivation of shallot seeds; 2) trial of shallot seed cultivation. This participatory action has succeeded in building and developing the capacity of farmers in Pejok Village to realize independence in shallot seedling.